The Integration of Vision, Mission, and Strategic Goals in Formulating Business and Corporate Strategies - Ega Aprilianti; Indah Kusuma Wati; Meli Yumita Sari; Syahdikin Syahdikin; Hanifah Riyanti; Aldi Saputra Hsb; Kuswanto Kuswanto; Sri Wahyuni; Ahmad Soleh (The Future of Education Journal, 2026)
Technological fluctuations and changes in government policies have created significant challenges for organizations in formulating relevant and adaptive strategies, particularly regarding vision, mission, and strategic goals. This article aims to examine how these three elements should be adapted to continuously evolving external factors, such as technological advancements and government policies. Using a Systematic Literature Review (SLR) method, this study analyzed 25 selected articles obtained from the Google Scholar and Emerald Insight databases. The findings reveal that organizations that successfully integrate external factors into their vision, mission, and strategic goals tend to be more effective in formulating responsive and flexible strategies. The study also highlights the importance of developing more dynamic strategic formulations, especially in addressing digital transformation and uncertainties in government policies. The main findings of this review indicate that organizations must pay greater attention to external factors in their strategic planning in order to survive and grow in an increasingly complex environment.